Mrs. O'Leary's cow - Hoberman, Mary Ann (Little, Brown and Co., 2007)
An adaptation of the well-known song, "There'll be a hot time in the old town tonight," based on the true story of the Great Chicago Fire. When Mrs. O'Leary leaves her lantern in the barn, the cow kicks it over and starts a fire. In this humorous story, the fire is put out in the end by 10 heroic firefighters.